2015
DOI: 10.1002/etc.3026
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced toxicity of Deepwater Horizon slick oil to blue crab (Callinectes sapidus) larvae

Abstract: The 2010 Deepwater Horizon oil spill resulted in the accidental release of approximately 700 million L of crude oil into the Gulf of Mexico. Photo-induced toxicity after co-exposure to ultraviolet (UV) radiation is 1 mechanism by which polycyclic aromatic hydrocarbons (PAHs) from oil spills may exert toxicity. Blue crab are an important commercial and ecological resource in the Gulf of Mexico, and their largely transparent larvae may make them sensitive to PAH photo-induced toxicity. The goal of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 33 publications
5
74
0
Order By: Relevance
“…All calculated tPAH 50 LC50s (0.18-5.78 mg /L) in the present study are within the lower range of PAH concentrations (0-84.8 mg/L) reported in the Deepwater Horizon spill area [29]. Deepwater Horizon spill oil, report total PAH median effective concentration (EC50) or LC50 values that are within an order of magnitude of those observed in the red drum and speckled seatrout tests [11,12,16,20]. (A) Mean percentage of mortality AE 1 standard error of larval speckled seatrout exposed to slick A high-energy water-accommodated fraction (HEWAF) and 1 of 3 ultraviolet (UV) treatments.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…All calculated tPAH 50 LC50s (0.18-5.78 mg /L) in the present study are within the lower range of PAH concentrations (0-84.8 mg/L) reported in the Deepwater Horizon spill area [29]. Deepwater Horizon spill oil, report total PAH median effective concentration (EC50) or LC50 values that are within an order of magnitude of those observed in the red drum and speckled seatrout tests [11,12,16,20]. (A) Mean percentage of mortality AE 1 standard error of larval speckled seatrout exposed to slick A high-energy water-accommodated fraction (HEWAF) and 1 of 3 ultraviolet (UV) treatments.…”
Section: Discussionsupporting
confidence: 79%
“…To account for differences in UV exposure, a phototoxic unit was calculated using methods similar to those of Oris and Giesy [5] and previously described in Alloy et al [12]. Tests not performed in parallel received different UV doses as a result.…”
Section: Phototoxic Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phototoxic doses were calculated using methods from Alloy et al and similar to Sellin Jeffries et al . To summarize, the concentrations of pPAH14 in each HEWAF sample were used in the calculations: anthracene; benzo[ a ]anthracene; benzo[ e ]pyrene; benzo[ g,h,i ]perylene; chrysene; fluoranthene; fluorene; C1 and C2 fluorenes; phenanthrene; C1‐, C2‐, and C3‐phenathrenes/anthracenes; and pyrene.…”
Section: Methodsmentioning
confidence: 99%
“…The RECOVER Consortium provides just such an opportunity in a cohesive unit. In previous work, we have shown that several native Gulf of Mexico species, including but not limited to early life stage crabs, mahi-mahi, and red drum are all sensitive to photo-induced PAH toxicity at concentrations well within the range observed during the DHOS (Figure 2) [61]. Funding provided by GoMRI will allow the multidisciplinary RECOVER team to continue to efficiently explore the mechanisms behind reduced survival of embryonic and larval stages of these species as well as potential mechanisms and outcomes of sublethal responses.…”
Section: Synergistic Effects Of Natural and Anthropogenic Stressorsmentioning
confidence: 75%